Neonatal (DISSEMINATED) listeriosis - M.L. Aryayev; N V. Kotova (Bukovynian State Medical University, 2013)
The epidemiology, etiology, pathogenesis, clinical manifestations, diagnosis, specific treatment and prophylaxis of neonatal listeriosis are presented in the lecture.